Spanish lecturers' beliefs about English medium instruction: STEM versus Humanities - Roothooft, Hanne (International journal of bilingual education and bilingualism, 2022)
More and more European universities are implementing English Medium Instruction (EMI) programs, but such policies tend to be top-down and pay insufficient attention to contextual factors such as the degree of internationalization of the universities involved, or the actual subject taught and the perceived role of English in that subject. To understand such contexts better, it is essential to listen to the voices of the professionals actually involved in the transition to EMI, namely the lecturers themselves. This study focuses specifically on EMI lecturers' beliefs in the Spanish context, and uses narrative frames to contrast the views of STEM and Humanities lecturers. In line with previous research, most of the 59 lecturers who completed our narrative frame indicated that they focused on content and not on language. Some differences in opinion between STEM and Humanities lecturers were found, especially with regard to changes in teaching style and L1 use. More Humanities teachers than STEM teachers felt that they had changed their teaching style. Humanities teachers also imposed stricter controls on L1 use, although overall attitudes to L1 use appeared to be determined more by other issues, such as the presence of international students, than by the actual subject in question.